A study of economics concepts in the Qur'an and the Sunnah. - Saleem, Muhammad Yusuf ([s.n], 2012)
This research paper investigates the meaning and implications of economic terms mentioned in the Qur’an and Sunnah. These include the concepts of human nature, balance (islah), disorder (fasad), justice (‘adl), poverty (faqr), sustenance (rizq), spending (infaq), extravagance (israaf), earning (kasb), unlawful (batil) acquisition of wealth, giving full measure, property (mal) and ownership (mikiyah). The meanings of these terms are investigated in both the classical as well as contemporary exegesis of the Qur’an and in the well-known collections of the hadith. The objectives of this research are to provide a thematic discussion of these concepts based on the relevant Qur’anic verses and ahadith and to contribute to efforts that are intended to construct an Islamic economic theory that is based on the Qur’an and the Sunnah. In order to provide a comprehensive understanding of these concepts a thematic methodology is employed in this research where the meaning and implications of each concept is examined in the various verses of the Qur’an and ahadith. As a second step the various exegesis of the Qur’an and the collections of ahadith are consulted on each particular concept.